The Process of Implementing Project-Based Learning in Science Learning for Class V of Quhas Jambi Elementary School - Nur Asiyah; Ilyas Idris; Andi Nurhasanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aimed to describe the implementation process of Project-Based Learning (PjBL) in Natural and Social Sciences (IPAS) learning for fifth-grade students at Madrasah Ibtidaiyah Quhas Jambi. The research employed a descriptive qualitative approach involving the fifth-grade homeroom teacher, students, the principal, and the vice principal for curriculum as research participants. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings revealed that the implementation of PjBL was carried out through planning, implementation, and project evaluation stages, which included students’ group collaboration, teacher guidance, and assessment throughout the project process. The application of PjBL had a positive impact on students’ activeness, creativity, and collaborative skills, although several challenges were identified, such as limited time, differences in students’ abilities, and inadequate learning facilities. The study concluded that PjBL had been implemented fairly well and supported the development of active and meaningful learning. This research contributes by providing empirical findings regarding the practical implementation of PjBL in elementary madrasah settings and can serve as a reference for teachers in designing more effective project-based learning. The implication suggests that teachers need to optimize guidance, time management, and the use of learning resources to enhance the effectiveness of PjBL implementation.